Certified Reference Material for Use in 1H, 31P, and 19F Quantitative NMR, Ensuring Traceability to the International System of Units. (22nd November 2019) - Rigger, Romana; Rück, Alexander; Hellriegel, Christine; Sauermoser, Robert; Morf, Fabienne; Breitruck, Kathrin; Obkircher, Markus
Abstract: In recent years, quantitative NMR (qNMR) spectroscopy has become one of the most important tools for content determination of organic substances and quantitative evaluation of impurities. Using Certified Reference Materials (CRMs) as internal or external standards, the extensively used qNMR method can be applied for purity determination, including unbroken traceability to the International System of Units (SI). The implementation of qNMR toward new application fields, e.g., metabolomics, environmental analysis, and physiological pathway studies, brings along morecomplex molecules and systems, thus making use of 1 H qNMR challenging. A smart workaround is possible by the use of other NMR active nuclei, namely 31 P and 19 F. This article presents the development of three classes of qNMR CRMs based on different NMR active nuclei ( 1 H, 31 P, and 19 F), and the corresponding approaches to establish traceability to the SI through primary CRMs from the National Institute of Standards and Technology and the National Metrology Institute of Japan. These Trace CERT ® qNMR CRMs are produced under ISO/IEC 17025 and ISO Guide 34 using high-performance qNMR.